Asynchronous Learning Networks: A Sloan Foundation Perspective - Mayadas, Frank (Online Learning, 1997)
This paper is based on a chapter in THE LEARNING REVOLUTION, the challenge of Information Technology in Academia (Diana G.Oblinger and Sean C. Rush, eds.), to be published this year by Anker Publishing Co., Boston, Mass. Over the years small numbers of motivated individuals have studied by themselves, away from university centers, to acquire knowledge in post-secondary subjects. Correspondence study began over a century ago and since then, other forms of "distance education" have become established. In spite of all this progress, off-campus learners have worked mainly in isolation, with only occasional contact with instructors and peers. Today’s low-cost communications and computer technologies, however, enable learning in Asynchronous Learning Networks (ALNs), in the process simultaneously overcoming barriers of isolation, distance and those imposed by rigid time constraints. The paper describes some projects at institutions of higher education funded by the Sloan Foundation, identifies some early results and possible evolution of ALN’s to large scale implementations.